UTILIZING PICTURE-BASED STORYTELLING TECHNIQUE TO ENHANCE THE SPEAKING SKILL - Muhammad Lukman Syafii (ETERNAL (English, Teaching, Learning and Research Journal), 2021)
With the researcher's impression of the business English course and the preliminary research conducted, the students' achievement in speaking skills was not satisfactory. To overcome this, the researcher proposes one of the appropriate techniques in speaking English by utilizing image-based storytelling techniques. This study aims to improve students' speaking skills by making use of those based images. The purpose of this study is to describe how image-based images can improve speaking skills of students in the accounting study program at Muhammadiyah University of Ponorogo. This research is a collaborative action research. This research was conducted cyclically by following action research procedures, namely planning, implementation, observation, and reflection. Each cycle consists of three meetings. Research data were collected through the following instruments: observation checklists, field notes, questionnaires, and students' performance in storytelling. The subjects of this study amounted to 36 people in the first academic semester. The research findings show that the use of picture-based storytelling techniques is effective in improving speaking achievement. This increase can be seen from the increase in students' moderate speaking ability from 55.42 in the preliminary study, and 59.46 in Cycle 1, to 75.92 in Cycle 2. In addition, the findings also show that the use of picture-based storytelling techniques is efficacious in improving interests and encouragement of students. This shows that in Cycle 1 there were 44% of students who participated actively and 93% of students who participated in Cycle 2. In addition, it was found that 80 percent of students were encouraged to apply storytelling techniques.